Criteria Assessment Model for Sustainable Product Development - Faiz, Mohd Turan; Kartina, Johan; Nik Hisyamudin, Muhd Nor (IOP Publishing, 2016)
The instability in today’s market and the ever increasing and emerging demands for mass customized and hybrid products by customers, are driving companies and decision makers to seek for cost effective and time efficient improvements in their product development process. Design concept evaluation which is the end of conceptual design is one of the most critical decision points in product development. It relates to the final success of product development, because poor criteria assessment in design concept evaluation can rarely compensated at the later stages. This has led to real pressure for the adaptation of new developmental architecture and operational parameters to remain competitive in the market. In this paper, a new integrated design concept evaluation based on fuzzy-technique for order preference by similarity to ideal solution (Fuzzy-TOPSIS) is presented, and it also attempts to incorporate sustainability practices in assessing the criteria. Prior to Fuzzy-TOPSIS, a new scale of “Weighting criteria” for survey process is developed to quantify the evaluation criteria. This method will help engineers to improve the effectiveness and objectivity of the sustainable product development. Case example from industry is presented to demonstrate the efficacy of the proposed methodology. The result of the example shows that the new integrated method provides an alternative to existing methods of design concept evaluation.